SNORD126 Promotes Hepatitis C Virus Infection by Upregulating Claudin-1 via Activation of PI3K-AKT Signaling Pathway - Qian, Xijing; Xu, Chen; Wu, Bingan; Tang, Hailin; Zhao, Ping; Qi, Zhongtian (Frontiers in Microbiology, 2020)
Hepatitis C virus (HCV) infection involves a variety of viral and host factors, some of which promote the infection process. A small nucleolar RNA, C/D box 126 (SNORD126), was previously shown to be associated with hepatocellular carcinoma (HCC). However, the role of SNORD126 in HCV infection, which is one of the primary reasons for HCC development, has not been elucidated. In the present study, using small nucleolar RNA profiling, we observed that SNORD126 was significantly downregulated during HCV infection in both Huh7 and Huh7.5.1 cells. In addition, overexpression of SNORD126 enhanced HCV entry into host cells, while SNORD126 knockdown showed the opposite effect, suggesting that SNORD126 promotes HCV infection, especially through viral entry. Further functional analysis revealed that SNORD126 could enhance the expression level of claudin-1 (CLDN1), a key HCV entry factor, by increasing the levels of phosphorylated AKT. Additionally, the function of SNORD126 in HCV infection was associated with ribonucleoprotein (RNP) complexes. In summary, our findings demonstrate that oncogenic SNORD126 levels are decreased during HCV infection probably due to the host defense reaction, and SNORD126 may be important to promote viral entry by increasing CLDN1 expression through activation of the PI3K-AKT pathway, the mechanism of which is partly associated with SNORD126-mediated snoRNA RNP (snoRNP) function. Our work here provides initial evidence that endogenous snoRNA takes part in HCV infection and shows potential as a diagnostic or antiviral agent.